From TORTORA to MegaTORTORA—Results and Prospects of Search for Fast Optical Transients - Grigory Beskin; Sergey Bondar; Sergey Karpov; Vladimir Plokhotnichenko; Adriano Guarnieri; Corrado Bartolini; Giuseppe Greco; Adalberto Piccioni; Andrew Shearer (Advances in Astronomy)
To study short stochastic optical flares of different objects (GRBs, SNs, etc.) of unknown localizations as well as NEOs it is necessary to monitor large regions of sky with high-time resolution. We developed a system consisting of widefield camera with field of view of 400–600 sq.deg. which uses TV-CCD with 0.13 s temporal resolution to record and classify optical transients, and a fast robotic telescope aimed to perform their spectroscopic and photometric investigation just after detection. Such two-telescope complex, combining wide-field camera TORTORA and robotic telescope REM, operated from May 2006 at La Silla ESO observatory. Some results of its operation, including first high time resolution study of optical transient accompanying GRB and discovery of its fine time structure, are presented. Also, prospects for improving the efficiency of such observations are given, and a project of a next generation wide field monitoring system, the MegaTORTORA, is described.